The role of foreign direct investment in technology development in Vietnam - Vinh Tuong Phi; Khanh Hung Tran; Viet Ha Hoang; Van-Chung Dong (Cogent Social Sciences)
Vietnam is regarded as one of the developing countries that successfully attracts foreign direct investment (FDI). Approaching and transferring technology in FDI projects is the top priority in promoting Vietnam’s FDI attractiveness strategy. The estimated results show that FDI positively contributed to technology development, stimulating innovation in science and technology applications while improving competitiveness for domestic enterprises. However, due to the lack of R&D activities and management capabilities, it still has numerous difficulties in applying and transferring technology to Vietnam. Therefore, to enhance the efficiency of FDI on technology development, Vietnam needs to strongly implement further solutions.